Developing Website-Based Multimedia for Self-Talk to Increase Self-Awareness Among Guidance and Counseling Students in the Special Region of Yogyakarta - Syarifudin; Suwarjo; Anisa Siti Nurjanah; Ida Rosyida (Universitas PGRI Yogyakarta, 2026)
Self-talk is one strategy that can increase self-awareness. This research aims to design a self-talk multimedia product that meets feasibility criteria and effectively increases students' self-awareness. Using the Borg and Gall development model, data were obtained through expert assessments, user ratings, and self-awareness scales, which were validated using Aiken's V and tested for reliability using Cronbach's Alpha. Qualitative analysis was carried out on validator and user suggestions, while quantitative analysis used feasibility percentages and t-tests. The results of the study show that multimedia self-talk is suitable for use, with 80% of media experts and 97.1% of material experts. Paired t-tests revealed significant improvements in self-awareness (p < 0.05; pretest = 72.49; posttest = 76). These findings prove that multimedia self-talk is effective in increasing students' self-awareness. The implication is that this product can be an innovation in technology-based guidance and counseling services that support students' learning independence and self-reflection. Kata kunci: multimedia, self-talk, self-awareness